Determinants of Vitamin D Status in Caucasian Adults: Influence of Sun Exposure, Dietary Intake, Sociodemographic, Lifestyle, Anthropometric, and Genetic Factors - Touvier, Mathilde; Deschasaux, Mélanie; Montourcy, Marion; Sutton, Angela; Charnaux, Nathalie; Kesse-Guyot, Emmanuelle; Assmann, Karen E.; Fezeu, Léopold; Latino-Martel, Paule; Druesne-Pecollo, Nathalie; Guinot, Christiane; Latreille, Julie; et al. (Journal of investigative dermatology, 2015)
Very few studies have investigated the determinants of serum vitamin D levels using a set of variables that include simultaneously sun exposure, phototype, dietary intake, sociodemographics, anthropometric, lifestyle data, and genetic polymorphisms. Our objective was to investigate the associations between all these parameters and vitamin D status in a large sample of French adults. This cross-sectional survey was based on 1,828 middle-aged Caucasian adults from the SU.VI.MAX (SUpplémentation en VItamines et Minéraux AntioXydants) study. Plasma 25-hydroxyvitamin D (25OHD) concentration was lower among women (P<0.0001), older subjects (P=0.04), obese/underweight (P<0.0001), those living at higher latitudes (P<0.0001), those whose blood draw occurred in early spring (P<0.0001), less physically active (P<0.0001), with low sun exposure (P<0.0001), and with no-to-low alcohol intake (P=0.0001). Mutant GC rs4588 and rs7041 single nucleotide polymorphisms were associated with lower and higher 25OHD concentrations, respectively (P<0.0001). Dietary intake was not a major determinant of vitamin D status (P=0.7). This study provides an overall picture of determinants of vitamin D status. Several modifiable factors were identified, such as daily-life moderate sun exposure, physical activity, and normal-weight maintenance, which should be targeted by public health policies in order to improve vitamin D status in the general population, while avoiding active/intensive sun exposure, in line with recommendations for skin cancer prevention.